Evaluation of Five-Day School Program Implementation Using the Model of Contex, Input, Process, and Product - Suharno Suharno; Budi Harjanto; Nita Murtia Handayani; N. Sutanti (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
This study aimed at evaluating the implementation of a five-day working program at vocational high schools. This study described the implementation, strengths, and weaknesses of the five-day working program in vocational high schools using a descriptive evaluative method with the model of Contex, Input, Process, and Product. This study was conducted in Vocational High Schools also known as Sekolah Menengah Kejuruan Negeri 2 Karanganyar. The sample of this study consisted of 126 students selected with a quota sampling technique and 10 teachers selected with a purposive sampling technique. Data were collected through observation, questionnaires, interviews, and documentation. The validity of the questionnaire item used logical validation. The results showed that the implementation of the five-day school program was sufficient but not fully achieved. The program can improve students' knowledge and skills and students’ activities are easier to be controlled. In the other hand, the school’ readiness to implement the five-day school program is not optimal indicated by not all teachers use interesting learning media and methods, and the teachers’ teaching performance during the day is decreased.